Polyethylene sealant film, laminate and packaging bag
Patent Information
- Application Number
- JP2021046054
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-19
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2041-03-19
AI Technical Summary
【0017】 本発明によれば、環境負荷低減性に優れると共に、耐衝撃性及び引き裂き性に優れる、ポリエチレン系シーラントフィルムを提供できる。 本発明によれば、該ポリエチレン系シーラントフィルムを備える積層体を提供できる。 本発明によれば、該積層体を備える包装袋を提供できる。
Smart Images

Figure 0007634164000004 
Figure 0007634164000005 
Figure 0007634164000006
Abstract
Description
[Technical field]
[0001] The present invention relates to a polyethylene sealant film, a laminate, and a packaging bag. [Background technology]
[0002] Conventionally, packaging bags have been used to fill and package contents such as food, medicines, chemicals, and cosmetics. The laminate constituting the packaging bag includes a base layer such as a stretched film and a sealant film having sealing properties. The packaging bag is manufactured by heat-sealing the sealant film provided in the laminate.
[0003] In recent years, with the growing demand for the creation of a recycling-oriented society, there is a desire to move away from fossil fuels in the materials field, just as there is in energy, and the use of biomass has attracted attention. Biomass is an organic compound that is photosynthesized from carbon dioxide and water, and by using it, it becomes carbon dioxide and water again, making it a so-called carbon-neutral renewable energy. Recently, the practical application of biomass plastics made from these biomass raw materials has progressed rapidly, and attempts are being made to produce various resins from biomass raw materials.
[0004] As a biomass-derived resin, polylactic acid (PLA), which is produced via lactic acid fermentation, was the first to be commercially produced, but since its performance as a plastic differs significantly from current general-purpose plastics, including its biodegradability, there are limitations to its product applications and manufacturing methods, and it has not yet become widely used.In addition, a life cycle assessment (LCA) is being conducted on PLA, and discussions are being held on the energy consumption during PLA production and its equivalence when replacing general-purpose plastics.
[0005] Here, various types of polymers such as polyethylene, polypropylene, polyvinyl chloride, polystyrene, and polyester are used as general-purpose plastics. In particular, polyethylene is molded into films, sheets, bottles, etc. and used for various purposes such as packaging materials, and is used in large quantities around the world, so using conventional polyethylene derived from fossil fuels places a large burden on the environment. Therefore, it is desirable to use raw materials derived from biomass in the production of polyethylene to reduce the amount of fossil fuels used. For example, research has been conducted to date on the production of ethylene and butylene, which are raw materials for polyolefin resins, from renewable natural raw materials (see Patent Document 1). [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Special Publication No. 2011-506628 Summary of the Invention [Problem to be solved by the invention]
[0007] It is desirable to use biomass-derived raw materials for sealant films to reduce the amount of fossil fuel used and the environmental impact. In addition, packaging bags are required to have tearability that allows them to be easily opened by hand and impact resistance that prevents them from being easily broken by external and internal impacts, and sealant films used for packaging bags are also required to have good impact resistance and tearability.
[0008] The present invention has been made in consideration of the above-mentioned points, and an object of the present invention is to provide a polyethylene sealant film that is excellent in reducing the environmental load, as well as in impact resistance and tear resistance. An object of the present invention is to provide a laminate comprising the polyethylene sealant film. An object of the present invention is to provide a packaging bag including the laminate. [Means for solving the problem]
[0009] The present invention provides a polyethylene sealant film having at least a laminate layer, an intermediate layer, and a seal layer in this order, The polyethylene sealant film contains a linear low-density polyethylene, The linear low density polyethylene includes an ethylene-1-butene copolymer and an ethylene-1-octene copolymer, the content of the ethylene-1-butene copolymer is greater than the content of the ethylene-1-octene copolymer, The intermediate layer is a polyethylene-based sealant film containing biomass polyethylene as a main component.
[0010] In the polyethylene-based sealant film according to the present invention, the sealing layer may contain linear low-density polyethylene.
[0011] The polyethylene sealant film according to the present invention may further comprise high pressure low density polyethylene.
[0012] In the polyethylene sealant film according to the present invention, the content of the ethylene-1-octene copolymer may be 30% by mass or less based on the entire sealant film.
[0013] In the polyethylene sealant film according to the present invention, the biomass content may be 50% or more.
[0014] The present invention provides a laminate comprising at least a base layer and a sealant layer, The sealant layer is a laminate comprising the polyethylene-based sealant film, the seal layer of the polyethylene-based sealant film being one surface layer of the laminate.
[0015] In the laminate according to the present invention, the base layer may be a stretched film.
[0016] The present invention is a packaging bag comprising the laminate. Effect of the Invention
[0017] According to the present invention, it is possible to provide a polyethylene sealant film that is excellent in reducing the environmental load and also has excellent impact resistance and tear resistance. According to the present invention, a laminate including the polyethylene sealant film can be provided. According to the present invention, a packaging bag including the laminate can be provided. [Brief description of the drawings]
[0018] [Figure 1] FIG. 1 is a schematic cross-sectional view showing one embodiment of a polyethylene sealant film according to the present invention. [Diagram 2] FIG. 2 is a plan view showing a test piece for evaluating impact strength. [Diagram 3] FIG. 2 is a schematic diagram showing a method for measuring impact strength. [Figure 4] FIG. 2 is a schematic diagram showing an example of a method for measuring puncture strength. [Diagram 5] 1 is a schematic cross-sectional view showing one embodiment of a laminate according to the present invention. [Figure 6] 1 is a schematic diagram showing one embodiment of a packaging bag according to the present invention. [Figure 7] 1 is a schematic diagram showing one embodiment of a packaging bag according to the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS The present invention will be described below with reference to the accompanying drawings, in which the scale and aspect ratios have been appropriately altered and exaggerated from those of the actual objects for the sake of illustration and ease of understanding.
[0020] In addition, terms used in this specification that specify shapes, geometric conditions, and the extent thereof, such as "orthogonal" and "same," as well as values of length and angle, are not bound by strict meanings, but are interpreted to include a range within which similar functions can be expected.
[0021] [Polyethylene sealant film] The polyethylene sealant film according to the present invention comprises a laminate layer, an intermediate layer, and a seal layer in this order, and contains linear low-density polyethylene. In the following, the polyethylene sealant film will also be simply referred to as "sealant film".
[0022] First, linear low density polyethylene (LLDPE) will be described. Linear low-density polyethylene is a copolymer of ethylene and an α-olefin polymerized using a multi-site catalyst such as a Ziegler-Natta catalyst or a single-site catalyst such as a metallocene catalyst. It has a viscosity of 0.930 g / cm 3 It is a polyethylene having a density of less than 0.900 g / cm. Therefore, it is distinguished from high-pressure low-density polyethylene (LDPE), which is a homopolymer of ethylene, as described below. The α-olefins that serve as monomers for linear low-density polyethylene have three or more carbon atoms, and examples of such monomers include propylene, 1-butene, 1-pentene, 1-hexene, 1-octene, 1-nonene, 4-methylpentene, and 3,3-dimethylbutene, as well as mixtures thereof. The content of α-olefin units in linear low-density polyethylene is, for example, 10 mol% or less, and may be 5 mol% or less. The density of linear low-density polyethylene is 0.900 g / cm. 3 More than that is fine. In this specification, the density of resins, layers, films, etc. is measured in accordance with Method B (pycnometer method) or Method D (density gradient tube method) of JIS K7112:1999. Method B or Method D is selected appropriately depending on the shape and mass of the test piece to be measured. In Method D, the measurement temperature (liquid temperature) is 23°C.
[0023] The single-site catalyst is a catalyst capable of forming a uniform active species, and is usually prepared by contacting a metallocene transition metal compound or a nonmetallocene transition metal compound with an activation cocatalyst. Compared with a multi-site catalyst, a single-site catalyst has a uniform active site structure, and therefore can polymerize a polymer having a high molecular weight and a highly uniform structure. Particularly preferred examples of the single-site catalyst include metallocene catalysts. The metallocene catalyst is a catalyst that includes a transition metal compound of Group IV of the periodic table containing a ligand having a cyclopentadienyl skeleton, a cocatalyst, and if necessary, an organometallic compound and each catalyst component of a carrier.
[0024] In the above-mentioned transition metal compound of Group IV of the periodic table containing a ligand having a cyclopentadienyl skeleton, the cyclopentadienyl skeleton is a cyclopentadienyl group, a substituted cyclopentadienyl group, etc. Examples of the substituted cyclopentadienyl group include those having at least one substituent selected from a hydrocarbon group having 1 to 30 carbon atoms, a silyl group, a silyl-substituted alkyl group, a silyl-substituted aryl group, a cyano group, a cyanoalkyl group, a cyanoaryl group, a halogen group, a haloalkyl group, a halosilyl group, etc. The substituted cyclopentadienyl group may have two or more substituents, and the substituents may be bonded to each other to form a ring, such as an indenyl ring, a fluorenyl ring, an azulenyl ring, or a hydrogenated product thereof. The rings formed by bonding the substituents to each other may further have substituents.
[0025] In the transition metal compound of Group IV of the periodic table containing a ligand having a cyclopentadienyl skeleton, the transition metal may be zirconium, titanium, hafnium, etc., and is particularly preferably zirconium and / or hafnium. The transition metal compound preferably has two ligands having a cyclopentadienyl skeleton, and each ligand having a cyclopentadienyl skeleton is bonded to each other by a bridging group. Examples of the bridging group include an alkylene group having 1 to 4 carbon atoms, a silylene group, a substituted silylene group such as a dialkylsilylene group or a diarylsilylene group, and a substituted germylene group such as a dialkylgermylene group or a diarylgermylene group. The bridging group is preferably a substituted silylene group.
[0026] In the transition metal compound of Group IV of the periodic table, examples of the ligand other than the ligand having a cyclopentadienyl skeleton include hydrogen, hydrocarbon groups having 1 to 20 carbon atoms (such as alkyl groups, alkenyl groups, aryl groups, alkylaryl groups, aralkyl groups, and polyenyl groups), halogens, metaalkyl groups, and metaaryl groups.
[0027] The above-mentioned compounds of transition metals of Group IV of the periodic table containing a ligand having a cyclopentadienyl skeleton can be used as the catalyst component either alone or in combination of two or more kinds.
[0028] The co-catalyst refers to a catalyst that can effectively use the above-mentioned transition metal compound of Group IV of the periodic table as a polymerization catalyst or balance the ionic charge in a catalytically activated state. Examples of the co-catalyst include benzene-soluble aluminoxanes of organoaluminum oxy compounds and benzene-insoluble organoaluminum oxy compounds, ion-exchangeable layered silicates, boron compounds, ionic compounds consisting of cations containing or not containing active hydrogen groups and non-coordinating anions, lanthanoid salts such as lanthanum oxide, tin oxide, and phenoxy compounds containing fluoro groups.
[0029] The transition metal compound of Group IV of the periodic table containing a ligand having a cyclopentadienyl skeleton may be used supported on an inorganic or organic carrier, preferably an inorganic or organic porous oxide, and specific examples of the carrier include ion-exchangeable layered silicates such as montmorillonite, SiO2, Al2O3, MgO, ZrO2, TiO2, B2O3, CaO, ZnO, BaO, ThO2, and mixtures thereof.
[0030] Further, the organometallic compound which is used if necessary is exemplified by organoaluminum compounds, organomagnesium compounds, organozinc compounds, etc. Of these, organoaluminum compounds are preferably used.
[0031] The content of the linear low-density polyethylene in the sealant film is, for example, 15% by mass or more, or may be 20% by mass or more, or 30% by mass or more, based on the entire sealant film, while the content of the linear low-density polyethylene in the sealant film is, for example, 70% by mass or less, or may be 50% by mass or less, based on the entire sealant film.
[0032] In the sealant film according to the present invention, the linear low density polyethylene contains an ethylene-1-butene copolymer and an ethylene-1-octene copolymer, and the content of the ethylene-1-butene copolymer is greater than the content of the ethylene-1-octene copolymer. That is, when the content of the ethylene-1-butene copolymer is C4 and the content of the ethylene-1-octene copolymer is C8, C4 and C8 satisfy the relationship C4>C8. Note that C4 and C8 are based on mass.
[0033] Among various linear low density polyethylenes, ethylene-1-butene copolymers have excellent tearability, but their impact resistance is inferior to other linear low density polyethylenes. The present invention realizes a sealant film that is excellent in both impact resistance and tearability by combining an ethylene-1-butene copolymer that has excellent tearability and an ethylene-1-octene copolymer that has better impact resistance than the ethylene-1-butene copolymer in a specific content relationship. In addition, the sealant film according to the present invention is excellent in both impact resistance and tearability by having a laminate layer, an intermediate layer, and a seal layer in this order. The mechanism by which such effects are obtained is not necessarily clear at present, but it is clear from the results of the examples and comparative examples described later that a sealant film having a laminate layer, an intermediate layer, and a seal layer, i.e., a sealant film composed of three or more layers, is superior in both impact resistance and tearability to sealant films composed of one layer and two layers.
[0034] The ratio of the content of the ethylene-1-octene copolymer to the content of the ethylene-1-butene copolymer is, for example, 0.05 or more, or may be 0.1 or more, or may be 0.3 or more, based on mass, whereas the ratio is, for example, 0.99 or less, or may be 0.9 or less, or may be 0.8 or less, based on mass.
[0035] Within the range satisfying the relationship C4>C8, the content of the ethylene-1-butene copolymer is preferably 5% by mass or more, more preferably 10% by mass or more, and even more preferably 15% by mass or more, based on the entire sealant film. By making the content of the ethylene-1-butene copolymer 5% by mass or more, the tearability of the sealant film can be improved. On the other hand, within the range satisfying the relationship C4>C8, the content of the ethylene-1-butene copolymer is, for example, 95 mass% or less, 92 mass% or less, 60 mass% or less, or 35 mass% or less, relative to the entire sealant film.
[0036] Within the range satisfying the relationship C4>C8, the content of the ethylene-1-octene copolymer is preferably 3% by mass or more, more preferably 5% by mass or more, and even more preferably 10% by mass or more, based on the entire sealant film. On the other hand, the content of the ethylene-1-octene copolymer is preferably 30% by mass or less, more preferably 25% by mass or less, and even more preferably 20% by mass or less, based on the entire sealant film. By making the content of the ethylene-1-octene copolymer 3% by mass or more, the impact resistance of the sealant film can be improved. On the other hand, by setting the content of the ethylene-1-octene copolymer to 30% by mass or less, the tearability of the sealant film can be improved.
[0037] In one embodiment, the sealant film may further contain high-pressure low-density polyethylene (LDPE). By containing high-pressure low-density polyethylene, the tearability of the sealant film can be further improved. In this specification, the high-pressure low-density polyethylene is 0.910 g / cm 3 More than 0.930g / cm 3 High-pressure low-density polyethylene is a homopolymer of ethylene having a density of less than 1,000 atm. High-pressure low-density polyethylene can be obtained, for example, by polymerizing ethylene under high pressure of 1,000 atm or more and less than 2,000 atm.
[0038] The content of the high-pressure low-density polyethylene is preferably 5% by mass or more, more preferably 10% by mass or more, based on the entire sealant film. By making the content of the high-pressure low-density polyethylene 5% by mass or more, the tearability of the sealant film can be further improved. On the other hand, the content of the high-pressure low-density polyethylene is, for example, 80% by mass or less, and may be 70% by mass or less, based on the entire sealant film.
[0039] Within the range satisfying the relationship C4>C8, the ratio of the content of the ethylene-1-octene copolymer to the total content of the ethylene-1-butene copolymer and the high-pressure low-density polyethylene in the sealant film is preferably 0.05 or more, more preferably 0.1 or more, on a mass basis, while the ratio is preferably 0.5 or less, more preferably 0.3 or less, on a mass basis. By setting the ratio to 0.05 or more, the impact resistance of the sealant film can be further improved. On the other hand, by setting the ratio to 0.5 or less, the tearability of the sealant film can be further improved.
[0040] The sealant film may contain high density polyethylene (HDPE) and / or medium density polyethylene (MDPE) as long as the object of the present invention is not impaired. In this specification, high density polyethylene means polyethylene having a density of 0.942 g / cm 3 Medium density polyethylene means polyethylene having a density of 0.930 g / cm or more. 3 More than 0.942g / cm 3 By "polyethylene" is meant polyethylene having a density less than 1000 MPa.
[0041] In one embodiment, the sealant film may contain biomass polyethylene. When the sealant film contains biomass polyethylene, the sealant film can improve its ability to reduce environmental impact. The content of biomass polyethylene in the sealant film is preferably 50% by mass or more, more preferably 60% by mass or more, based on the entire sealant film. On the other hand, the content of biomass polyethylene in the sealant film may be, for example, 90% by mass or less, or 80% by mass or less, based on the entire sealant film. As used herein, biomass polyethylene refers to a polymer of a monomer composition containing ethylene derived from biomass. The monomer composition may also contain ethylene derived from conventional fossil fuels. An example of a method for producing ethylene derived from biomass will be described below.
[0042] Biomass-derived ethylene can be produced using biomass-derived ethanol as a raw material. In particular, it is preferable to use biomass-derived fermented ethanol obtained from a plant raw material. The plant raw material is not particularly limited, and any conventionally known plant can be used. Examples of the plant raw material include corn, sugarcane, beet, and manioc.
[0043] Fermented ethanol derived from biomass refers to ethanol produced by contacting a culture solution containing a carbon source obtained from a plant raw material with an ethanol-producing microorganism or a product derived from the crushed microorganism, and then purifying the ethanol. Conventionally known methods such as distillation, membrane separation, and extraction can be applied to purify ethanol from the culture solution. For example, there is a method of adding benzene, cyclohexane, etc., and removing water by azeotropy or membrane separation.
[0044] In order to obtain the above ethylene, the ethanol may be further subjected to advanced purification at this stage, for example, so that the total amount of impurities in the ethanol is reduced to 1 ppm or less.
[0045] A catalyst is usually used when obtaining ethylene by the dehydration reaction of ethanol, but the catalyst is not particularly limited and any conventionally known catalyst can be used. From the viewpoint of the process, a fixed bed flow reaction is advantageous because it is easy to separate the catalyst from the product, and for example, γ-alumina is preferable.
[0046] This dehydration reaction is an endothermic reaction, and is therefore usually carried out under heating conditions. As long as the reaction proceeds at a commercially useful reaction rate, the heating temperature is not limited, but is preferably 100° C. or higher, more preferably 250° C. or higher, and even more preferably 300° C. or higher. There is no particular upper limit, but from the viewpoint of energy balance and equipment, it is preferably 500° C. or lower, and more preferably 400° C. or lower.
[0047] In the dehydration reaction of ethanol, the yield of the reaction depends on the amount of water contained in the ethanol supplied as a raw material. In general, when performing a dehydration reaction, it is preferable to have no water in consideration of the efficiency of removing water. However, in the case of the dehydration reaction of ethanol using a solid catalyst, it has been found that the amount of other olefins, especially butene, produced tends to increase in the absence of water. It is presumed that this is because ethylene dimerization after dehydration cannot be suppressed without the presence of a small amount of water. The lower limit of the allowable water content is 0.1% by mass or more, and preferably 0.5% by mass or more. The upper limit is not particularly limited, but from the viewpoint of material balance and heat balance, it is preferably 50% by mass or less, more preferably 30% by mass or less, and even more preferably 20% by mass or less.
[0048] By carrying out the dehydration reaction of ethanol in this manner, a mixture of ethylene, water, and a small amount of unreacted ethanol is obtained, but since ethylene is in a gaseous state at room temperature under approximately 5 MPa or less, water and ethanol can be removed from the mixture by gas-liquid separation to obtain ethylene. This can be done by a known method.
[0049] The ethylene obtained by the gas-liquid separation is further distilled. The distillation method, operation temperature, residence time, etc. are not particularly limited, except that the operation pressure at this time is normal pressure or higher.
[0050] When the raw material is biomass-derived ethanol, the obtained ethylene contains trace amounts of carbonyl compounds such as ketones, aldehydes, and esters, which are impurities mixed in during the ethanol fermentation process, as well as carbon dioxide gas, which is a decomposition product thereof, and nitrogen-containing compounds such as amines and amino acids, which are enzyme decomposition products and impurities, as well as ammonia, which is a decomposition product thereof. Depending on the use of ethylene, these trace amounts of impurities may be problematic, so they may be removed by purification. The purification method is not particularly limited, and can be performed by a conventionally known method. An example of a suitable purification operation is an adsorption purification method. The adsorbent used is not particularly limited, and a conventionally known adsorbent can be used. For example, a material with a high surface area is preferable, and the type of adsorbent is selected according to the type and amount of impurities in the ethylene obtained by the dehydration reaction of biomass-derived ethanol.
[0051] In addition, a caustic water treatment may be used in combination as a method for purifying impurities in ethylene. When using caustic water treatment, it is preferable to perform the treatment before adsorption purification. In that case, it is necessary to perform a water removal treatment after the caustic treatment and before the adsorption purification.
[0052] The inclusion of biomass polyethylene in the sealant film of the present invention can be determined by measuring the biomass content of the sealant film. When the sealant film contains biomass polyethylene, the biomass content of the sealant film is greater than 0%.
[0053] Here, the biomass degree will be described. Carbon dioxide in the atmosphere contains a certain percentage of C14 (105.5 pMC), so it is known that the C14 content in plants that grow by absorbing carbon dioxide from the atmosphere, such as corn, is also about 105.5 pMC. It is also known that fossil fuels contain very little C14. Therefore, by measuring the percentage of C14 in the total carbon atoms, the percentage of carbon derived from biomass can be calculated. The "biomass degree" indicates the weight ratio of biomass-derived components. For example, in the case of polyethylene terephthalate, polyethylene terephthalate is a polymer of ethylene glycol containing two carbon atoms and terephthalic acid containing eight carbon atoms in a molar ratio of 1:1. Therefore, when only biomass-derived ethylene glycol is used, the weight ratio of biomass-derived components in the polyester is 31.25%, so the theoretical value of the biomass degree is 31.25%. Specifically, the mass of polyethylene terephthalate is 192, of which the mass derived from biomass-derived ethylene glycol is 60, so 60÷192×100=31.25. In addition, the weight ratio of biomass-derived components in the fossil fuel polyester produced using fossil fuel-derived ethylene glycol and fossil fuel-derived dicarboxylic acid is 0%, so the biomass degree of the fossil fuel polyester is 0%. Hereinafter, unless otherwise specified, the "biomass degree" indicates the weight ratio of biomass-derived components.
[0054] Theoretically, if only biomass-derived raw materials were used as the raw material for polyethylene, the concentration of biomass-derived ethylene would be 100%, and therefore the biomass content of biomass polyethylene would be 100%. The concentration of biomass-derived ethylene in fossil fuel polyethylene, which is produced only from fossil fuel-derived raw materials, is 0%. Therefore, the biomass content of fossil fuel-derived polyethylene is 0%.
[0055] From the viewpoint of reducing the environmental load, the biomass degree of the sealant film is preferably 50% or more, more preferably 60% or more, whereas the biomass degree of the sealant film is, for example, 90% or less, and may be 80% or less.
[0056] The thickness of the sealant film is, for example, 20 μm or more, or may be 70 μm or more, or 100 μm or more, while the thickness of the sealant film is, for example, 300 μm or less, or may be 200 μm or less, or may be 150 μm or less.
[0057] The sealant film may contain one or more additives as long as the object of the present invention is not impaired. Examples of additives include plasticizers, UV stabilizers, color inhibitors, matting agents, deodorants, flame retardants, weather resistance agents, antistatic agents, friction reducers, slip agents, antiblocking agents, antioxidants, ion exchange agents, and color pigments. The sealant film preferably contains a slip agent and / or an antiblocking agent.
[0058] Hereinafter, one embodiment of the polyethylene sealant film according to the present invention will be described with reference to FIG.
[0059] In one embodiment, the polyethylene sealant film 10 is composed of a laminate layer 11, an intermediate layer 12, and a seal layer 13, as shown in Fig. 1. As shown in Fig. 1, the seal layer 13 is one surface layer of the polyethylene sealant film 10, and the laminate layer 11 is the other surface layer of the polyethylene sealant film 10.
[0060] Each layer of the polyethylene sealant film according to the present invention will be described below.
[0061] <Laminate layer> The laminate layer is a layer that constitutes one of the surface layers of the sealant film, and is a layer that is located on the base layer side of the laminate when the sealant film is used in the laminate.
[0062] In one embodiment, the laminate layer contains linear low density polyethylene. This can improve the impact resistance of the sealant film. In addition, since the laminate layer contains linear low density polyethylene, when the sealant film is used in a laminate, the adhesion with other layers can be improved. The linear low density polyethylene contained in the laminate layer may contain an ethylene-1-butene copolymer, or may contain at least one copolymer selected from the group consisting of an ethylene-1-butene copolymer and an ethylene-1-octene copolymer.
[0063] From the viewpoint of the impact resistance of the sealant film and adhesion to other layers, the content of the linear low-density polyethylene in the laminate layer is preferably 50% by mass or more, more preferably 60% by mass, and even more preferably 70% by mass or more, based on the entire laminate layer. On the other hand, the content of the linear low-density polyethylene in the laminate layer is, for example, 95% by mass or less, or may be 90% by mass or less, or may be 85% by mass or less, based on the entire laminate layer.
[0064] The laminate layer may contain high-pressure low-density polyethylene, which can improve the tearability of the sealant film.
[0065] From the viewpoint of tearability of the sealant film, the content of the high-pressure low-density polyethylene in the laminate layer is preferably 3% by mass or more, more preferably 8% by mass or more, and even more preferably 13% by mass or more, based on the entire laminate layer. On the other hand, the content of the high-pressure low-density polyethylene in the laminate layer is, for example, 45% by mass or less, or may be 35% by mass or less, or may be 25% by mass or less, based on the entire laminate layer.
[0066] The thickness of the laminate layer is, for example, 5 μm or more, or may be 10 μm or more, or may be 15 μm or more, whereas the thickness of the laminate layer is, for example, 70 μm or less, or may be 50 μm or less, or may be 35 μm or less.
[0067] The laminate layer may contain high density polyethylene (HDPE) and / or medium density polyethylene (MDPE) as long as the object of the present invention is not impaired.
[0068] In one embodiment, the laminate layer may include biomass polyethylene.
[0069] The laminate layer may contain one or more additives as long as the object of the present invention is not impaired. Examples of additives include plasticizers, UV stabilizers, color inhibitors, matting agents, deodorants, flame retardants, weather resistance agents, antistatic agents, friction reducers, slip agents, antiblocking agents, antioxidants, ion exchange agents, and color pigments. The laminate layer preferably contains a slip agent.
[0070] The surface of the sealant film on the laminate layer side may be subjected to a surface treatment, which can improve adhesion to other layers. The method of surface treatment is not particularly limited, and examples thereof include physical treatments such as corona treatment, flame treatment, ozone treatment, low-temperature plasma treatment using oxygen gas and / or nitrogen gas, and glow discharge treatment, as well as chemical treatments such as oxidation treatment using chemicals.
[0071] <Sealing layer> The sealing layer is a layer that constitutes the other surface layer of the sealant film. In addition, when the sealant film is used in a laminate, the sealing layer is a layer that constitutes one surface layer of the laminate or both surface layers of the laminate, and is a layer that is fused by heat.
[0072] In one embodiment, the seal layer contains linear low density polyethylene. This can improve the impact resistance of the sealant film. In addition, since the seal layer contains linear low density polyethylene, the heat fusion temperature can be lowered and the sealability of the sealant film can be improved. The linear low density polyethylene contained in the seal layer may contain an ethylene-1-octene copolymer, or may contain at least one copolymer selected from the group consisting of an ethylene-1-butene copolymer and an ethylene-1-octene copolymer.
[0073] The content of the linear low-density polyethylene in the seal layer is preferably 50% by mass or more, more preferably 60% by mass or more, and even more preferably 70% by mass or more, based on the entire seal layer, from the viewpoint of the impact resistance and sealability of the sealant film. On the other hand, the content of the linear low-density polyethylene in the seal layer is, for example, 95% by mass or less, or may be 90% by mass or less, or may be 85% by mass or less, based on the entire seal layer.
[0074] The sealing layer may contain high-pressure low-density polyethylene, which can improve the tearability of the sealant film.
[0075] From the viewpoint of tearability of the sealant film, the content of the high-pressure low-density polyethylene in the seal layer is preferably 3% by mass or more, more preferably 8% by mass or more, and even more preferably 13% by mass or more, based on the entire seal layer. On the other hand, the content of the high-pressure low-density polyethylene in the laminate layer is, for example, 45% by mass or less, or may be 35% by mass or less, or may be 25% by mass or less, based on the entire seal layer.
[0076] The thickness of the sealing layer is, for example, 5 μm or more, or may be 10 μm or more, or may be 15 μm or more, while the thickness of the sealing layer is, for example, 70 μm or less, or may be 50 μm or less, or may be 35 μm or less.
[0077] The thickness ratio of the laminate layer to the seal layer is preferably 0.5 to 2, more preferably 0.8 to 1.2, and particularly preferably 0.9 to 1.1. By setting the thickness ratio in this range, the phenomenon in which the sealant film warps, i.e., the so-called curl phenomenon, can be suppressed.
[0078] The sealing layer may contain high density polyethylene (HDPE) and / or medium density polyethylene (MDPE) without impairing the object of the present invention.
[0079] In one embodiment, the sealing layer may include biomass polyethylene.
[0080] The sealing layer may contain one or more additives as long as the object of the present invention is not impaired. Examples of additives include plasticizers, UV stabilizers, color inhibitors, matting agents, deodorants, flame retardants, weather resistance agents, antistatic agents, friction reducers, slip agents, antiblocking agents, antioxidants, ion exchange agents, and color pigments. The sealing layer preferably contains a slip agent and / or an antiblocking agent.
[0081] <Middle Class> The intermediate layer is a layer located between the seal layer and the laminate layer. The intermediate layer may be a single layer or multiple layers. When the intermediate layer is a multiple layer, the composition of each intermediate layer may be the same or different.
[0082] In the sealant film according to the present invention, the intermediate layer contains biomass polyethylene as a main component, thereby realizing a sealant film with excellent environmental load reduction properties. In this specification, the term "main component" refers to a component that is contained in an amount of 50% by mass or more.
[0083] From the viewpoint of reducing the environmental load, the content of biomass polyethylene in the intermediate layer is preferably 70% by mass or more, more preferably 90% by mass or more, and even more preferably 95% by mass or more, based on the entire intermediate layer.
[0084] The intermediate layer may contain linear low density polyethylene and / or high pressure low density polyethylene. From the viewpoint of the impact resistance of the sealant film, the intermediate layer preferably contains linear low density polyethylene. On the other hand, from the viewpoint of the tearability of the sealant film, the intermediate layer preferably contains high pressure low density polyethylene.
[0085] In the intermediate layer, the biomass polyethylene is preferably linear low density polyethylene and high pressure low density polyethylene.
[0086] The thickness of the intermediate layer is, for example, 10 μm or more, or may be 50 μm or more, or 70 μm or more, while the thickness of the intermediate layer is 160 μm or less, or may be 100 μm or less, or may be 80 μm or less.
[0087] The thickness of the intermediate layer is preferably thicker than that of the laminate layer. This can suppress curling of the sealant film. The ratio of the thickness of the intermediate layer to the thickness of the laminate layer is preferably 1 to 10, more preferably 2 to 5. The thickness of the intermediate layer is preferably thicker than that of the sealing layer. This can suppress curling of the sealant film. The ratio of the thickness of the intermediate layer to the thickness of the sealing layer is preferably 1 to 10, more preferably 2 to 5.
[0088] The intermediate layer may contain high density polyethylene (HDPE) and / or medium density polyethylene (MDPE) as long as the object of the present invention is not impaired.
[0089] The intermediate layer may contain one or more additives as long as the object of the present invention is not impaired. Examples of additives include plasticizers, ultraviolet stabilizers, color inhibitors, matting agents, deodorants, flame retardants, weather resistance agents, antistatic agents, friction reducers, slip agents, antiblocking agents, antioxidants, ion exchange agents, and color pigments. The intermediate layer preferably contains a slip agent.
[0090] <Characteristics of sealant film> In the sealant film according to the present invention, the value I obtained by dividing the impact strength by the thickness of the sealant film is, for example, 0.0023 J / μm or more, and may be 0.0028 J / μm or more, while the value I is, for example, 0.01 J / μm or less, and may be 0.004 J / μm or less. In this specification, the impact strength of the sealant film is measured in accordance with ASTM D3420. For example, a film impact tester BU-302 manufactured by Tester Sangyo Co., Ltd. can be used as a measuring device. In this specification, unless otherwise specified, the environment during the measurement of the impact strength is a temperature of 23°C and a relative humidity of 90% RH.
[0091] The method for measuring the impact strength will be described with reference to Figures 2 and 3. First, as shown in Figure 2, a test piece 20 is clamped and fixed between ring-shaped jigs 21 and 22. Next, as shown in Figure 3, the fixed test piece 20 is placed, and an arm 24 is swung down around a fulcrum 23, so that the conical indenter 25 at the tip of the arm 24 breaks through the test piece 20, and the strength at the time of breakthrough is measured. Measurements are carried out on five test pieces, and the average value is taken as the impact strength. The diameter of the indenter 25 is about 1 inch (about 25.4 mm), the load is about 30 kg cm, and the lifting angle of the arm is about 90°.
[0092] In the sealant film according to the present invention, the value T obtained by dividing the tear strength by the thickness of the sealant film is, for example, 0.01 N / μm or more, and may be 0.03 N / μm or more, in at least one direction, whereas the value T is, for example, 0.1 N / μm or less, and may be 0.07 N / μm or less, in at least one direction. In one embodiment, the value T is, for example, 0.01 N / μm or more, and may be 0.03 N / μm or more, in the machine direction (MD) of the film, while the value T is, for example, 0.1 N / μm or less, and may be 0.07 N / μm or less, in the machine direction (MD) of the film. In this specification, the tear strength of the sealant film is measured in accordance with the Elmendorf tear method of JIS K7128-2:1998. For example, an Elmendorf tear tester IM-701 manufactured by Tester Sangyo Co., Ltd. can be used as a measuring device. Measurement is performed on five test pieces, and the average value is taken as the tear strength. In this specification, unless otherwise specified, the environment during the measurement of tear strength is a temperature of 23°C and a relative humidity of 90% RH.
[0093] The breaking strength of the sealant film according to the present invention is, for example, 10 MPa or more, and may be 20 MPa or more, in at least one direction, whereas the breaking strength of the sealant film is, for example, 50 MPa or less, and may be 30 MPa or less, in at least one direction. In one embodiment, the breaking strength of the sealant film in MD is, for example, 10 MPa or more, and may be 20 MPa or more, whereas the breaking strength of the sealant film in MD is, for example, 50 MPa or less, and may be 30 MPa or less. In one embodiment, the breaking strength of the sealant film in the direction perpendicular to the machine direction (TD) of the film is, for example, 10 MPa or more, and may be 20 MPa or more, whereas the breaking strength of the sealant film in the TD is, for example, 50 MPa or less, and may be 30 MPa or less.
[0094] The breaking elongation of the sealant film according to the present invention is, for example, 400% or more, and may be 500% or more, in at least one direction, while the breaking elongation of the sealant film is, for example, 900% or less, and may be 700% or less, in at least one direction. In one embodiment, the breaking elongation of the sealant film in MD is, for example, 400% or more, and may be 500% or more, whereas the breaking elongation of the sealant film in MD is, for example, 900% or less, and may be 700% or less. In one embodiment, the breaking elongation of the sealant film in TD is, for example, 400% or more, and may be 500% or more, whereas the breaking elongation of the sealant film in TD is, for example, 900% or less, and may be 700% or less.
[0095] In this specification, the breaking strength and breaking elongation of the sealant film are measured in accordance with JIS Z1702:1994. For example, a Tensilon universal material testing machine RTC-1530 manufactured by Orientec Co., Ltd. can be used as a measuring instrument. A sealant film cut into a dumbbell shape can be used as a test piece. The measurement width of the test piece is 5 mm, the distance between a pair of chucks holding the test piece at the start of the measurement is 80 mm, and the tensile speed is 500 mm / min. Measurement is performed on five test pieces, and the average values are taken as the breaking strength and breaking elongation. The length of the test piece can be changed as long as the test piece can be held by a pair of chucks. In this specification, unless otherwise specified, the environment during measurement of the breaking strength and breaking elongation is a temperature of 23°C and a relative humidity of 90% RH.
[0096] In the sealant film according to the present invention, the value P obtained by dividing the puncture strength by the thickness of the sealant film is, for example, 0.02 N / μm or more, and may be 0.03 N / μm or more, while the value P is, for example, 0.1 N / μm or less, and may be 0.05 N / μm or less. In this specification, the puncture strength of the sealant film is measured in accordance with JIS Z1707:2019. For example, a Tensilon universal material testing machine RTC-1530 manufactured by Orientec Co., Ltd. can be used as a measuring instrument. In this specification, unless otherwise specified, the environment during the measurement of the puncture strength is a temperature of 23°C and a relative humidity of 90% RH.
[0097] The method for measuring the puncture strength will be described with reference to Fig. 4. As shown in Fig. 4, a semicircular needle 31 with a diameter of 1.0 mm and a tip radius of 0.5 mm is pierced into a fixed test piece 30 at a speed of 50 mm / min, and the maximum stress until the needle 31 penetrates the test piece 30 is measured. The maximum stress is measured for five test pieces, and the average value is taken as the puncture strength of the sealant film.
[0098] [Method for producing sealant film] The method for producing the sealant film according to the present invention is not particularly limited, and can be produced by a conventionally known method. The sealant film is preferably co-extruded, and more preferably, the co-extrusion is performed by a T-die method or an inflation method. Hereinafter, an example of the method for producing the sealant film by the T-die method or the inflation method will be described.
[0099] In the T-die method, first, the materials constituting each layer are dried, and then fed into a melt extruder heated to a temperature above the melting point (Tm) to Tm+100°C, where they are melted and extruded into a sheet from the T-die. The extruded sheet is then quenched and solidified on a rotating cooling drum or the like to form a sealant film. As the melt extruder, a single screw extruder, a twin screw extruder, a vent extruder, a tandem extruder, etc. can be used depending on the purpose.
[0100] In the inflation method, the materials constituting each layer are first dried, and then fed into a melt extruder heated to a temperature (Tm) to Tm+100°C above the melting point, where they are melted and extruded into a cylindrical shape through an annular die. At this time, air is fed into the cylindrical molten resin from below to expand the diameter of the cylinder to a predetermined size, and cooling air is fed from below to the outside of the cylinder. This expanded cylindrical body is called a bubble. Next, the bubble is folded into a film shape by a guide plate and a pinch roll, and wound up in a winding section. The folded film may be wound up as it is in a cylindrical shape, or both ends of the cylinder may be removed by a slitter or the like, cut into two pieces of film, and then each may be wound up. In this way, a sealant film can be formed. As the melt extruder, a single screw extruder, a twin screw extruder, a vent extruder, a tandem extruder, etc. can be used depending on the purpose.
[0101] [Laminate] The laminate according to the present invention comprises at least a base layer and a sealant layer. In the laminate according to the present invention, the sealant layer comprises the sealant film according to the present invention, and the seal layer of the polyethylene sealant film is one of the surface layers of the laminate. Since the laminate according to the present invention comprises the sealant film according to the present invention, it is excellent in reducing environmental load and has excellent impact resistance and tear resistance. Hereinafter, the layer structure of the laminate according to the present invention will be described with reference to FIG.
[0102] In one embodiment, the laminate 40 includes a base layer 41 and a sealant layer 42, as shown in Fig. 5. As shown in Fig. 5, the sealant layer 42 is a sealant film 10 including a laminate layer 11, an intermediate layer 12, and a seal layer 13. As shown in Fig. 5, the sealant layer 13 of the sealant film 10 is one surface layer of the laminate 40.
[0103] A laminate according to the invention may comprise further layers located on the other surface of the laminate or between each layer.
[0104] Next, each layer that may be included in the laminate of the present invention will be described. Note that the sealant layer is a layer that includes the sealant film of the present invention, and the sealant film has been described above. Therefore, the description of the sealant layer will be omitted.
[0105] <Base material layer> The substrate layer is a layer having a function of supporting the laminate. For example, a paper-based resin film or a laminate thereof can be appropriately used as the substrate layer.
[0106] The paper base material may be one having printability, flex resistance, rigidity, stiffness, strength, etc., and may be any of a variety of papers such as kraft paper, roll paper, paperboard, and processed paper.
[0107] The resin film contains at least one resin material. Examples of resin materials contained in the resin film include polyesters such as polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polyethylene naphthalate (PEN), 1,4-polycyclohexylene dimethylene terephthalate, and terephthalic acid-cyclohexanedimethanol-ethylene glycol copolymers; polyamides such as nylon 6, nylon 6,6, and polymetaxylylene adipamide (MXD6); polyolefins such as polyethylene (PE), polypropylene (PP), and polymethylpentene; vinyl resins such as polyvinyl chloride, polyvinyl alcohol (PVA), polyvinyl acetate, vinyl chloride-vinyl acetate copolymers, polyvinyl butyral, and polyvinylpyrrolidone (PVP); (meth)acrylic resins such as polyacrylate, polymethacrylate, and polymethyl methacrylate; cellulose resins such as cellophane, cellulose acetate, nitrocellulose, cellulose acetate propionate (CAP), and cellulose acetate butyrate (CAB); styrene resins such as polystyrene (PS), and chlorinated resins thereof. Among these, the resin material contained in the resin film is preferably at least one selected from the group consisting of polyolefin, polyester, and polyamide, and more preferably at least one selected from the group consisting of polypropylene, polyethylene terephthalate, nylon 6, and nylon 6,6.
[0108] The resin film may be a stretched film or an unstretched film. From the viewpoint of strength, the resin film is preferably a uniaxially or biaxially stretched film.
[0109] The surface of the resin film may be subjected to the above-mentioned surface treatment.
[0110] The thickness of the base layer is, for example, 5 μm or more, and may be 10 μm, whereas the thickness of the base layer is, for example, 200 μm or less, and may be 100 μm or less, or may be 50 μm or less.
[0111] <Other layers> The other layers are located on the other surface of the laminate or between the layers, and include, for example, an adhesive layer, a printing layer, a support layer, and a barrier layer.
[0112] The adhesive layer is an adhesive layer or adhesive resin layer formed to bond two layers together by lamination.
[0113] The adhesive layer is a layer formed using at least one type of one-liquid or two-liquid curable or non-curable laminating adhesive. Therefore, the adhesive layer includes a laminating adhesive. Examples of laminating adhesives include vinyl-based, (meth)acrylic-based, polyamide-based, polyester-based, polyether-based, polyurethane-based, epoxy-based, and rubber-based solvent-based, water-based, or emulsion-based laminating adhesives. Examples of methods for coating the adhesive include a direct gravure roll coating method, a gravure roll coating method, a kiss coating method, a reverse roll coating method, a Fontaine method, and a transfer roll coating method. The coating amount is, for example, 0.1 g / m in a dry state. 2 More than 1g / m 2 On the other hand, the coating amount is, for example, 10 g / m2 in a dry state. 2 Less than 5 g / m 2 A lower rank would be fine too.
[0114] The adhesive resin layer contains at least one thermoplastic resin. Examples of the thermoplastic resin contained in the adhesive resin layer include high-pressure low-density polyethylene, medium-density polyethylene, high-density polyethylene, linear low-density polyethylene, ethylene-vinyl acetate copolymer, ethylene-acrylic acid copolymer, ethylene-ethyl acrylate copolymer, ethylene-methacrylic acid copolymer, ethylene-methyl methacrylate copolymer, ethylene-maleic acid copolymer, and ionomer resin. Examples of the thermoplastic resin contained in the adhesive resin layer include resins obtained by graft-polymerizing or copolymerizing unsaturated carboxylic acid, unsaturated carboxylic acid anhydride, and ester monomer to polyolefin, and resins obtained by graft-modifying maleic anhydride to polyolefin. The thermoplastic resin may be made of a material derived from a fossil fuel, a material derived from biomass, or a combination of both.
[0115] The print layer is an image formed using a conventionally known pigment or dye. Examples of the image include characters, patterns, symbols, and combinations thereof. The print layer can be formed by a conventionally known method.
[0116] The support layer is a layer that supports the laminate together with the base layer and improves the strength characteristics, durability, and the like of the laminate.
[0117] The support layer contains one or more resin materials. Examples of resin materials contained in the support layer include polyesters such as polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polyethylene naphthalate (PEN), 1,4-polycyclohexylene dimethylene terephthalate, and terephthalic acid-cyclohexanedimethanol-ethylene glycol copolymers; polyamides such as nylon 6, nylon 6,6, and polymetaxylylene adipamide (MXD6); polyolefins such as polyethylene (PE), polypropylene (PP), and polymethylpentene; vinyl resins such as polyvinyl chloride, polyvinyl alcohol (PVA), polyvinyl acetate, vinyl chloride-vinyl acetate copolymers, polyvinyl butyral, and polyvinylpyrrolidone (PVP); (meth)acrylic resins such as polyacrylate, polymethacrylate, and polymethyl methacrylate; cellulose resins such as cellophane, cellulose acetate, nitrocellulose, cellulose acetate propionate (CAP), and cellulose acetate butyrate (CAB); styrene resins such as polystyrene (PS), and chlorinated resins thereof. The support layer may be a resin film made of the above-mentioned resin material. From the viewpoint of strength, the resin film is preferably a film stretched in a uniaxial or biaxial direction.
[0118] The barrier layer is a layer for imparting excellent gas barrier properties to the laminate. A laminate including a barrier layer has excellent barrier properties against gases such as oxygen and water vapor.
[0119] In one embodiment, the barrier layer may include a vapor-deposited film of an inorganic substance or an inorganic oxide, such as one or more inorganic substances such as silicon (Si), aluminum (Al), magnesium (Mg), calcium (Ca), potassium (K), tin (Sn), sodium (Na), boron (B), titanium (Ti), lead (Pb), zirconium (Zr), and yttrium (Y), or a vapor-deposited film of an inorganic oxide thereof. The vapor-deposited film can be formed on the surface of the base layer and / or support layer, etc. Examples of methods for forming the vapor-deposited film include known methods such as vacuum deposition, sputtering, and chemical vapor deposition.
[0120] The thickness of the evaporated film is, for example, 10 nm or more, and may be 20 nm or more, whereas the thickness of the evaporated film is, for example, 200 nm or less, and may be 100 nm or less.
[0121] In one embodiment, the barrier layer may include a gas barrier coating film located on the surface of the vapor-deposited film. When the barrier layer includes a gas barrier coating film, the gas barrier properties can be further improved.
[0122] The gas barrier coating film is represented by the general formula R 1 n M(OR 2 ) m (In the formula, R 1 , R 2 represents an organic group having 1 to 8 carbon atoms, M represents a metal atom, n represents an integer of 0 or more, m represents an integer of 1 or more, and n+m represents the atomic valence of M. The gas barrier composition contains at least one alkoxide represented by the formula (I) and the above-mentioned polyvinyl alcohol resin and / or ethylene-vinyl alcohol copolymer, and is further polycondensed by a sol-gel method in the presence of a sol-gel catalyst, an acid, water, and an organic solvent.
[0123] The above general formula R 1 n M(OR 2 ) m As the alkoxide represented by the formula (I), at least one of a partial hydrolyzate of an alkoxide and a condensate of hydrolysis of an alkoxide can be used. As the partial hydrolyzate of an alkoxide, it is not necessary that all of the alkoxy groups are hydrolyzed, and one or more alkoxy groups may be hydrolyzed, or a mixture thereof. As the condensate of hydrolysis of an alkoxide, a dimer or more of a partially hydrolyzed alkoxide, preferably a dimer or more and a hexamer or less, is used.
[0124] The above general formula R 1 n M(OR 2 ) m In the alkoxide represented by the formula (I), silicon, zirconium, titanium, aluminum, and the like can be used as the metal atom represented by M. Preferred metals include, for example, silicon and titanium. The alkoxide may be used alone or in the form of a mixture of two or more different metal atoms in the same solution.
[0125] The above general formula R 1 n M(OR 2 ) m In the alkoxide represented by the formula: 1 Specific examples of the organic group represented by the general formula R include alkyl groups such as methyl, ethyl, n-propyl, i-propyl, n-butyl, i-butyl, sec-butyl, t-butyl, n-hexyl, and n-octyl. 1 n M(OR 2 ) m In the alkoxide represented by the formula: 2 Specific examples of the organic group represented by the formula (I) include a methyl group, an ethyl group, an n-propyl group, an i-propyl group, an n-butyl group, a sec-butyl group, etc. These alkyl groups may be the same or different in the same molecule.
[0126] When preparing the gas barrier composition, for example, a silane coupling agent may be added. As the silane coupling agent, a known organoalkoxysilane containing an organic reactive group may be used. In particular, an organoalkoxysilane having an epoxy group may be preferably used. As the organoalkoxysilane having an epoxy group, for example, γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropylmethyldiethoxysilane, or β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane may be mentioned. The silane coupling agent may be used alone or in a mixture of two or more kinds.
[0127] In one embodiment, the barrier layer may include a metal foil. The metal foil is a foil containing one or more metal materials. Examples of the metal materials contained in the metal foil include aluminum, gold, silver, copper, stainless steel, titanium, and nickel. The metal foil can be laminated to the base layer and / or support layer, etc. via an adhesive layer.
[0128] [Packaging bag] The packaging bag according to the present invention includes the laminate according to the present invention. The laminate according to the present invention is excellent in reducing the environmental load and has excellent impact resistance and tear resistance, so that a packaging bag including the laminate is excellent in reducing the environmental load and has excellent impact resistance and tear resistance.
[0129] Fig. 6 is a schematic diagram showing one embodiment of a packaging bag according to the present invention. As shown in Fig. 6, packaging bag 50 includes body 51 and bottom 52. Body 51 is composed of two side sheets 53, and bottom 52 is composed of a bottom sheet 54. In packaging bag 50, side sheets 53 use laminate 40 according to the present invention. Therefore, packaging bag 50 is manufactured such that seal layer 13 of sealant layer 41 of laminate 40 becomes the innermost layer. In addition, the side sheets 53 and the bottom sheet 54 of the packaging bag 50 may be made of the same material or different materials.
[0130] The packaging bag 50 may include a pouring nozzle portion 55 as shown in Fig. 7. Moreover, the packaging bag 50 may include a curved portion 56 that is curved inward from the viewpoint of ease of opening as shown in Fig. 7. Furthermore, the packaging bag 50 may include a cutout portion 57 from the viewpoint of ease of opening as shown in Fig. 7. The cutout portion 57 can be formed by irradiating a laser beam or the like. 9 and 10, the hatched areas indicate the heat-sealed areas.
[0131] Since the packaging bag according to the present invention has excellent tearability, it is particularly preferable that the bag is provided with a cut-out portion 57 as shown in FIG.
[0132] The contents of the packaging bag are not particularly limited, but because of its excellent impact resistance, the packaging bag is particularly suitable for packaging liquids such as shampoo, conditioner, and detergent. EXAMPLES
[0133] Next, the present invention will be described more specifically with reference to examples. However, the present invention is not limited to the description of the following examples as long as it does not depart from the gist of the present invention.
[0134] The materials used in the examples are listed below. (1) Ethylene-1-butene copolymer (4LLDPE_A) ··· Density: 0.918g / cm 3 , MFR: 1.0g / 10min, Biomass content: 87%, Braskem, SLL118 (2) Ethylene-1-butene copolymer (4LLDPE_B) ··· Density: 0.918g / cm 3 , MFR: 4.0g / 10min, Biomass content: 0%, Ube Maruzen Polyethylene Co., Ltd., Yumerit 722FT (3) Ethylene-1-octene copolymer (8LLDPE_A) ··· Density: 0.918 g / cm 3 , MFR: 0.85g / 10min, Biomass content: 0%, Dow, INNATE ST50 (4) Ethylene-1-octene copolymer (8LLDPE_B) ··· Density: 0.916g / cm 3 , MFR: 1.0g / 10min, Biomass content: 0%, Dow, ELITE 5400G (5) High-pressure low-density polyethylene (LDPE_A) ··· Density: 0.923 g / cm 3 , MFR: 2.7g / 10min, Biomass content: 95%, Braskem, SEB853 (6) High-pressure low-density polyethylene (LDPE_B) ··· Density: 0.919 g / cm 3 , MFR: 2.0g / 10min, Biomass ratio: 0%, Sumitomo Chemical Co., Ltd., G201-F (7) Masterbatch (MB_A) Base material: polyethylene, slip agent: erucic acid amide, slip agent content: 2.0 mass%, density: 0.921 g / cm 3 , MFR: 5.4g / 10min, Ube Maruzen Polyethylene Co., Ltd., M425 (8) Masterbatch (MB_B) Base material: polyethylene, antiblocking agent: talc, slip agent: erucic acid amide, antiblocking agent content: 6.0 mass%, slip agent content: 1.5 mass%, density: 0.959 g / cm 3 , MFR: 2.5g / 10min, Ube Maruzen Polyethylene Co., Ltd., M615S
[0135] [Example 1] A mixture of 80 parts by mass of 4LLDPE_B, 19 parts by mass of LDPE_A, and 1 part by mass of MB_A was used as the laminate layer, a mixture of 99 parts by mass of LDPE_A and 1 part by mass of MB_A was used as the intermediate layer, and a mixture of 79 parts by mass of 8LLDPE_A, 19 parts by mass of LDPE_A, and 2 parts by mass of MB_B was used as the seal layer. The mixture was melted and co-extruded into a film to obtain a polyethylene sealant film consisting of three layers. The thickness of the polyethylene sealant film is 130 μm. The thickness ratio of the laminate layer:intermediate layer:seal layer is 1:3:1.
[0136] [Example 2] A polyethylene sealant film was obtained in the same manner as in Example 1, except that a mixture of 50 parts by mass of 4LLDPE_B, 30 parts by mass of 8LLDPE_A, 19 parts by mass of LDPE_A, and 1 part by mass of MB_A was used as the laminate layer, and a mixture of 49 parts by mass of 4LLDPE_B, 30 parts by mass of 8LLDPE_A, 19 parts by mass of LDPE_A, and 2 parts by mass of MB_B was used as the seal layer.
[0137] [Example 3] A polyethylene sealant film was obtained in the same manner as in Example 1, except that a mixture of 50 parts by mass of 4LLDPE_B, 30 parts by mass of 8LLDPE_B, 19 parts by mass of LDPE_A, and 1 part by mass of MB_A was used as the laminate layer, and a mixture of 50 parts by mass of 4LLDPE_B, 30 parts by mass of 8LLDPE_B, 19 parts by mass of LDPE_A, and 1 part by mass of MB_B was used as the seal layer.
[0138] [Example 4] A polyethylene sealant film was obtained in the same manner as in Example 1, except that a mixture of 50 parts by mass of 4LLDPE_A, 30 parts by mass of 8LLDPE_A, 19 parts by mass of LDPE_A, and 1 part by mass of MB_A was used as the laminate layer, and a mixture of 50 parts by mass of 4LLDPE_B, 29 parts by mass of 8LLDPE_B, 19 parts by mass of LDPE_A, and 2 parts by mass of MB_B was used as the seal layer.
[0139] [Example 5] A polyethylene sealant film was obtained in the same manner as in Example 1, except that a mixture of 79 parts by mass of 4LLDPE_B, 20 parts by mass of 8LLDPE_A, and 1 part by mass of MB_A was used as the laminate layer, a mixture of 99 parts by mass of 4LLDPE_A and 1 part by mass of MB_A was used as the intermediate layer, and a mixture of 79 parts by mass of 4LLDPE_B, 19 parts by mass of 8LLDPE_A, and 2 parts by mass of MB_B was used as the seal layer.
[0140] [Example 6] A polyethylene sealant film was obtained in the same manner as in Example 1, except that a mixture of 79 parts by mass of 4LLDPE_B, 20 parts by mass of 8LLDPE_B, and 1 part by mass of MB_A was used as the laminate layer, a mixture of 99 parts by mass of 4LLDPE_A and 1 part by mass of MB_A was used as the intermediate layer, and a mixture of 79 parts by mass of 4LLDPE_B, 19 parts by mass of 8LLDPE_B, and 2 parts by mass of MB_B was used as the seal layer.
[0141] [Comparative Example 1] A polyethylene sealant film was obtained in the same manner as in Example 1, except that a mixture of 80 parts by mass of 8LLDPE_A, 19 parts by mass of LDPE_A, and 1 part by mass of MB_A was used as the laminate layer.
[0142] [Comparative Example 2] A polyethylene sealant film was obtained in the same manner as in Example 1, except that a mixture of 80 parts by mass of 8LLDPE_B, 19 parts by mass of LDPE_A, and 1 part by mass of MB_A was used as the laminate layer.
[0143] [Comparative Example 3] A polyethylene sealant film was obtained in the same manner as in Example 1, except that a mixture of 79 parts by mass of 4LLDPE_B, 19 parts by mass of LDPE_A, and 2 parts by mass of MB_B was used as the sealing layer.
[0144] [Comparative Example 4] A polyethylene sealant film was obtained in the same manner as in Example 1, except that a mixture of 99 parts by mass of 4LLDPE_B and 1 part by mass of MB_A was used as the laminate layer, a mixture of 99 parts by mass of 4LLDPE_A and 1 part by mass of MB_A was used as the intermediate layer, and a mixture of 98 parts by mass of 4LLDPE_B and 2 parts by mass of MB_B was used as the seal layer.
[0145] [Comparative Example 5] A mixture of 24 parts by mass of 4LLDPE_B, 75 parts by mass of 8LLDPE_B, and 1 part by mass of MB_A was used as the laminate layer, and a mixture of 80 parts by mass of 4LLDPE_A, 18 parts by mass of 8LLDPE_A, and 2 parts by mass of MB_B was used as the seal layer. The mixture was melted and co-extruded into a film to obtain a polyethylene sealant film consisting of two layers. The thickness of the polyethylene sealant film was 130 μm. The thickness ratio of the laminate layer to the seal layer was 3:1.
[0146] [Comparative Example 6] A polyethylene sealant film was obtained in the same manner as in Comparative Example 5, except that a mixture of 24 parts by mass of 4LLDPE_B, 75 parts by mass of LDPE_A, and 1 part by mass of MB_A was used as the laminate layer, and a mixture of 28 parts by mass of 4LLDPE_B, 70 parts by mass of 8LLDPE_B, and 2 parts by mass of MB_B was used as the seal layer.
[0147] [Comparative Example 7] A polyethylene sealant film was obtained in the same manner as in Comparative Example 5, except that a mixture of 24 parts by mass of 4LLDPE_B, 75 parts by mass of LDPE_A, and 1 part by mass of MB_A was used as the laminate layer, and a mixture of 28 parts by mass of 4LLDPE_B, 70 parts by mass of 8LLDPE_A, and 2 parts by mass of MB_B was used as the seal layer.
[0148] [Comparative Example 8] A mixture of 70 parts by mass of 4LLDPE_A, 19 parts by mass of 8LLDPE_B, 10 parts by mass of LDPE_B, and 1 part by mass of MB_B was melted and extruded into a film to obtain a single-layer polyethylene sealant film. The thickness of the polyethylene sealant film is 130 μm.
[0149] [Comparative Example 9] A polyethylene sealant film was obtained in the same manner as in Comparative Example 8, except that a mixture of 70 parts by mass of 4LLDPE_A, 19 parts by mass of 8LLDPE_A, 10 parts by mass of LDPE_B, and 1 part by mass of MB_B was used.
[0150] [Comparative Example 10] A polyethylene sealant film was obtained in the same manner as in Comparative Example 8, except that a mixture of 39 parts by mass of 8LLDPE_B, 60 parts by mass of LDPE_A, and 1 part by mass of MB_B was used.
[0151] [Comparative Example 11] A polyethylene sealant film was obtained in the same manner as in Comparative Example 8, except that a mixture of 39 parts by mass of 8LLDPE_A, 60 parts by mass of LDPE_A, and 1 part by mass of B_B was used.
[0152] [Comparative Example 12] A polyethylene sealant film was obtained in the same manner as in Comparative Example 8, except that a mixture of 39 parts by mass of 4LLDPE_B, 60 parts by mass of LDPE_A, and 1 part by mass of MB_B was used.
[0153] Details of the polyethylene sealant films obtained in the examples and comparative examples are shown in Table 1.
[0154] [Table 1]
[0155] <<Measurement of impact strength>> The impact strength of the sealant films of the Examples and Comparative Examples was measured in accordance with ASTM D 3420. The measuring device used was a film impact tester BU-302 manufactured by Tester Sangyo Co., Ltd. Specifically, first, as shown in FIG. 2, the test piece 20 was fixed by clamping it between ring-shaped jigs 21 and 22. Next, as shown in FIG. 3, the fixed test piece 20 was placed, and the arm 24 was swung down around the fulcrum 23, so that the conical indenter 25 at the tip of the arm 24 broke through the test piece 20, and the strength at the time of breaking through was measured. Measurements were performed on five test pieces, and the average value was taken as the impact strength. The diameter of the indenter 25 was about 1 inch (about 25.4 mm), the load was about 30 kg cm, and the lifting angle of the arm was about 90°. The environment during the impact strength measurement was a temperature of 23°C and a relative humidity of 90% RH. The measurement results are shown in Table 2. In addition, the impact strength was divided by the thickness of the sealant film to calculate the value I. The calculation results are shown in Table 2.
[0156] <<Tear strength measurement>> The tear strength of the sealant films of the examples and comparative examples was measured in accordance with the Elmendorf tear method of JIS K7128-2:1998. The measuring device used was an Elmendorf tear tester IM-701 manufactured by Tester Sangyo Co., Ltd. Measurements were performed on five test pieces, and the average value was taken as the tear strength. The impact strength was measured in an environment of a temperature of 23°C and a relative humidity of 90% RH. The measurement results are shown in Table 2. In Table 2, "over" means that measurement was not possible. The tear strength was divided by the thickness of the sealant film to calculate the value T. The calculation results are shown in Table 2.
[0157] <<Measurement of breaking strength and breaking elongation>> The breaking strength and breaking elongation of the sealant films of the Examples and Comparative Examples were measured in accordance with JIS Z1702: 1994. The measuring device used was a Tensilon universal material testing machine RTC-1530 manufactured by Orientec Co., Ltd. The test pieces used were sealant films cut into dumbbell shapes. The measurement width of the test pieces was 5 mm, the distance between the pair of chucks holding the test pieces at the start of the measurement was 80 mm, and the tensile speed was 300 mm / min. Measurements were performed on five test pieces, and the average values were taken as the breaking strength and breaking elongation. The environment during the measurement of the breaking strength and breaking elongation was a temperature of 23°C and a relative humidity of 90% RH. The measurement results are shown in Table 2.
[0158] <<Puncture strength measurement>> The puncture strength of the sealant films of the Examples and Comparative Examples was measured in accordance with JIS Z1707: 2019. The measuring instrument used was a Tensilon universal material testing machine RTC-1530 manufactured by Orientec Co., Ltd. Specifically, as shown in FIG. 4, a semicircular needle 31 with a diameter of 1.0 mm and a tip radius of 0.5 mm was pierced into a test piece 30 in a fixed state at a speed of 50 mm / min, and the maximum stress value until the needle 31 penetrated the test piece 30 was measured. The maximum stress values were measured for five test pieces, and the average value was taken as the piercing strength of the sealant film. The piercing strength was measured in both the case where the test piece was pierced from the laminate layer side and the case where the seal layer side was pierced. The environment during the piercing strength measurement was a temperature of 23° C. and a relative humidity of 90% RH. The measurement results are shown in Table 2. In addition, the puncture strength was divided by the thickness of the sealant film to calculate the value P. The calculation results are shown in Table 2.
[0159] [Table 2]
[0160] <<Evaluation of environmental impact reduction>> The sealant films in the examples and comparative examples were evaluated for their ability to reduce environmental impact based on the following evaluation criteria. The evaluation results are shown in Table 3. ·Good: Contains biomass-derived materials. · No Good: Does not contain any biomass-derived materials.
[0161] <<Impact resistance evaluation>> The impact resistance of the sealant films in the examples and comparative examples was evaluated based on the following evaluation criteria. The evaluation results are shown in Table 3. · Good: Impact strength is 0.35J or more. · No Good: The impact strength is less than 0.35J.
[0162] <<Evaluation of tearability>> The tearability of the sealant films in the examples and comparative examples was evaluated based on the following evaluation criteria. The evaluation results are shown in Table 3. ·Good: The tear strength in MD is less than 8N. · No Good: The tear strength in MD is 8N or more.
[0163] [Table 3]
[0164] The sealant film according to the present invention is excellent in reducing the environmental load, and is also excellent in impact resistance and tear resistance. [Explanation of symbols]
[0165] 10: Polyethylene sealant film 11: Laminate layer 12: Middle class 13: Sealing layer 20: Test piece 21, 22: Jig 23: Support part 24: Arm 25: Indenter 30: Test piece 31: Needle 40: Laminate 41: Base material layer 42: Sealant layer 50: Packaging bag 51: Torso 52: Bottom 53: Side sheet 54: Bottom sheet 55: Nozzle for pouring 56: Curved section 57: Cut-out section
Claims
1. A polyethylene sealant film comprising at least a laminate layer, an intermediate layer, and a seal layer in this order, The polyethylene sealant film contains a linear low-density polyethylene, The linear low density polyethylene includes an ethylene-1-butene copolymer and an ethylene-1-octene copolymer, the content of the ethylene-1-butene copolymer is greater than the content of the ethylene-1-octene copolymer, The intermediate layer contains biomass polyethylene as a main component, The intermediate layer is a polyethylene-based sealant film that does not contain high density polyethylene.
2. The polyethylene-based sealant film of claim 1 , wherein the sealing layer comprises a linear low density polyethylene.
3. The polyethylene sealant film according to claim 1 or 2, further comprising a high-pressure low-density polyethylene.
4. The polyethylene sealant film according to any one of claims 1 to 3, wherein the content of the ethylene-1-octene copolymer is 30 mass% or less based on the entire sealant film.
5. The polyethylene sealant film according to any one of claims 1 to 4, having a biomass degree of 50% or more.
6. A laminate comprising at least a base layer and a sealant layer, The sealant layer comprises the polyethylene-based sealant film according to any one of claims 1 to 5, and the seal layer of the polyethylene-based sealant film is one surface layer of the laminate.
7. The laminate according to claim 6 , wherein the substrate layer is a stretched film.
8. A packaging bag comprising the laminate according to claim 6 or 7.
Citation Information
Patent Citations
Multilayer film
JP1986078645A
Polyethylene multilayered film to be metallized
JP1994270357A
Integrated method for the production of ethylene-butylene copolymer, ethylene-butylene copolymer and use of ethylene and 1-butylene as comonomers supplied from renewable natural raw materials.
JP2011506628A
White sealant film and package comprising the same
JP2018020496A
White sealant film and package comprising the same
JP2018020544A